Co3(SO4)3(OH)2[enH 2]: A New S = 3/2 kagome-type layered sulfate with a unique connectivity - Powell, Anthony V. (2009)
The versatile method of structure-directed synthesis in a sulfuric acid system for the preparation of novel metal sulfates including those with structures comprising vertex-linked M(O,F)6 octahedra with a Kagome topology was explored. Terminal atoms of the sulfate anions are directed above and below the layers into the inter-layer space, where diprotonated ethylenediamine cations, which further balance the anionic charges of the layers and provide linkage between layers through an extensive network of hydrogen bonds between amino cations. The effective magnetic moment per cobalt ion decreases on cooling from 300 to 12 K, owing to a combination of a reduction in the orbital contribution and anti-ferromagnetic correlations. Interaction between clusters which are geometrically frustrated Interaction introduced the considerable complexity into the macroscopic magnetic behavior, where the degree of complexity in the material will necessitate detailed neutron measurements as a function of temperature.